Performance enhancement and economic analysis of pyramid solar still with corrugated absorber plate and conventional solar still: A case study - Emad Ghandourah; Hitesh Panchal; Othman Fallatah; Haitham M. Ahmed; Essam B. Moustafa; Ammar H. Elsheikh (Case Studies in Thermal Engineering, 2022)
Solar energy is utilized to convert brackish or saline water into drinking water in solar stills. Recent years have seen a lot of attention paid to developing new designs for solar stills to overcome the constraints of the lower yield. Pyramid solar still (PSS) is a design of solar still having triangular glass cover to receive sun rays. The present research article shows enhancement of the yield of the PSS by increasing the evaporation area by using corrugated plate. Due to the addition of corrugated sheet as absorber plate, it is called as pyramid solar still with corrugated absorber plate (PSSCAP). Its performance has compared with conventional solar still (CSS) in climate conditions of Patan, Gujarat, India, from March to July 2018. The experimental results revealed that the yield of PSSCAP is found higher than that of a CSS due to the corrugated absorber due to increment of water temperature. According to the results, the yield of PSSCAP found 4.5 L/day, whereas the yield of CSS was 2.95 L/day. A comparative study found that the PSSCAP produced a 52.54% higher yield than a CSS due to the corrugated sheet used as an absorber plate. Furthermore, the average thermal efficiency for the PSSCAP and the CSS found 45.5% and 31.5%, respectively. The estimated cost of 1L of yield for a PSSCAP and a CSS is approximately 0.53 and 0.68 INR, respectively, from research work.